Evaluasi Kesesuaian Perencanaan dan Realisasi Pekerjaan Peningkatan Jalan Pangkalan-Batas Jambi Kecamatan Rawas Ulu, Kabupaten Musi Rawas Utara - Heru Fahrudin Faiz; Rika Ampuh Hadiguna (Fakultas Teknik Universitas Cenderawasih, 2026)
Road improvement projects require consistency between technical planning documents and field implementation to ensure that service quality, structural performance, construction time, and user safety are achieved. This article evaluates the conformity between planning and realization in the Pangkalan-Batas Jambi road improvement project in Rawas Ulu District, North Musi Rawas Regency. The study used a descriptive-quantitative evaluative approach based on field monitoring, project technical documents, comparative quantity analysis between contract and Contract Change Order (CCO), and identification of implementation constraints. The results showed that several work items changed during construction because initial planning data did not fully capture actual field conditions. Quantities increased for drainage excavation (+18.87%), roadbed preparation (+8.99%), aggregate class A base course (+12.51%), and AC-Base (+11.98%). Conversely, reinforced pipe culverts decreased (-58.33%), unsealed aggregate base/sirtu decreased (-43.50%), and tack/prime coat volume slightly decreased (-0.47%). The time schedule showed a minor delay of -0.13% in the first week but recovered in the second week, indicating effective field coordination. Main constraints included traffic interference, limited worker visibility, and equipment visibility. The study recommends more detailed site surveys during planning, stronger traffic management, stricter occupational safety implementation, systematic progress control, and routine post-construction maintenance to maintain road service life.